The Impact of Green Human Resource Management on Employees’ Eco-Friendly Behavior: The Mediating Roles of Green Transformational Leadership and Green Perceived Organizational Support - Riza Yonita; Deni Suwandhani; Thesa Alif Ravelby; Muthia Roza Linda; Siti Norashikin Bashirun; Suhery (Jurnal Ecogen, 2026)
This study examines the relationship between Green Human Resource Management (GHRM) and employees’ Eco-Friendly Behavior (EFB), with Green Transformational Leadership (GTFL) and Green Perceived Organizational Support (GPOS) serving as mediating variables. We adopted quantitative research design and surveyed employees in four- and five-star hotels using structured questionnaires. We collected 240 responses through purposive sampling; however, only 110 were valid and met the criteria for further analysis. We analyzed the data using Structural Equation Modeling (SEM) in SmartPLS. The findings reveal that GHRM practices have a positive and significant effect on GPOS and GTFL Furthermore, GTFL has a positive and significant effect on EFB, whereas GPOS does not. Additionally, GTFL has a positive and significant effect on GPOS. These results highlight the critical role of leadership in enhancing GHRM's effectiveness in promoting eco-friendly behavior among employees. This study contributes to the growing body of literature on sustainable human resource management and provides practical implications for the hospitality industry in fostering environmentally responsible behavior.